ナンキョク ショウワキチ ダイ10 キョジュウトウ ノ パネル コウセイザイ ノ ケイネン ヘンカ ト タイキュウセイ - 小西, 敏正; コニシ, トシマサ; 中村, 成春; ナカムラ, シゲハル; 大島, 隆一; オオシマ, リュウイチ; 工藤, 大樹; クドウ, タイキ; 田中, 亮司; タナカ, リョウジ; Konishi, Toshimasa; Nakamura, Shigeharu; et al. (2002)
P(論文) 南極において恒久観測基地として利用された昭和基地第10居住棟(高床式木質パネル構造:1969年1月建設)の一部を復元・解体し、特にその木質パネルの構成材に観点をおいて、約30年間使用された建物の各部位における耐久性を把握することを目的とした。試験は、目視による観察・木材試験・断熱材性能試験を行い、その結果、各部位には壁・床に比べて屋根パネルの構成材の劣化が最も激しく、また極地という厳しい条件下では、パネル構成材の耐久性は特にパネル間の接合部に大きく起因すること、また室内部やパネル内部は30年間使用してもほとんど劣化しないことが明らかになった。 The purpose of this study is to determine the durability of the old living hut built in 1969 at Syowa Station, Japan's permanent Antarctic observation facility, especially of its wooden panels. The hut, of high floor type wooden panel construction, was built in January 1969. To determine the durability, part of the hut, which was brought back to Japan after 30 years, was rebuilt, then taken apart again under controlled test conditions. Tests included visual observation, testing of the wooden material, and testing of the performance of the thermal insulation material. The results showed that the material in the roof panels deteriorated considerably more than that in the walls and floors. In the severe polar conditions, the strength of the overall structure depends heavily on the joints between panels. It is clear that material on the indoor sides, and in the interiors of the panels, hardly deteriorated at all after 30 years. departmental bulletin paper